Defense and security policies of the brazilian's cyberspace from the “campaign manual - Guerra Cibernética” (Research, Society and Development, 2020)
With the constant evolution of technology, societies have become increasingly dependent on technological tools, many of which make up what is called cyberspace. Therefore, is presented a research that aims to understand the positioning of the Brazilian State in relation to Security and Defense of National Cyberspace. In this sense, bibliographic research and documentary analysis were carried out. The bibliographic research operated with knowledge about cyberspace and International Relations theories while the documentary analysis detailed the Campaign Manual – Guerra Cibernética, published in 2017. At the end of the process, it is highlighted that the Brazilian State has limited documentation regarding theme and in these few documents, efficient strategies to contain threats related to the defense of national cyberspace are not evident, as it is a prescriptive and non-strategic document. In this way, it is evident that the Brazilian State is hostage to situations which may threaten the sovereignty of its cyberspace, making it necessary to face issues related to cyber security and defense in Brazil with more importance and attention.